Determinant of Bank Risk with Bank Scale as Moderating Variable in ASEAN - Susy Muchtar; Adler Haymans Manurung; Farah Margaretha (GoAcademica Research & Publishing, 2021)
This research examines the determinant of bank risk with Bank Scale as the moderating variable. The determinants of bank risk in the study are Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Loan to Deposit Ratio (LDR), Market Power (MP), Exchange Rate (ER), Interest Rate (IR), and Technology Investment (TI). Standard Deviation (STD) and Value at Risk (VaR) are proxies of bank risk. The bank scale is based on Bank Umum Kelompok Usaha (BUKU Bank). The unit of research analysis are conventional banks listed on the Stock Exchange of ASEAN-4 countries namely Indonesia Malaysia, Philippines, and Thailand during the period of 2010 - 2019 with a total of 35 banks. Panel data regression is used to determine bank risk. The examination was conducted on banks in ASEAN-4 countries and Indonesia. The results found that banks in ASEAN-4 countries: CAR, MP, ER, IR, TI, and BB have significant negative effect on STD and LDR have significant negative effect on VaR, MP and TI have significant positive effect on VaR. For banks in Indonesia, ER positively affects STD, IR and IT negatively affect STD, NPL positively affects VaR, LDR and TI negatively affect VaR. BB has no effect on bank risk. The results of this study are expected to contribute in bank management to pay attention on bank-specific variables, especially technology investments and macroeconomic variables due to their enormous influence in increasing profitability and lowering risks.